Structural characterization and immunomodulatory activity of a new heteropolysaccharide from Prunella vulgaris. Issue 5 (13th May 2015) - Li, Chao; You, Lijun; Fu, Xiong; Huang, Qiang; Yu, Shujuan; Liu, Rui Hai
<x xml:space="preserve">Abstract</x> A new heteropolysaccharide, here called P1, was isolated from the fruit clusters of Prunella vulgaris using a hot water extraction method.